The first 107 presidential decrees, conquest to proclamation nos. 1081/1104 - Pinpin, F . D. , comp ([Mandaluyong Rizal, Philippines] : Cacho Hermanos, 1973)
--------. Presidential decree nos. 108-227 and related documents ... Bk. two xiv, 656p. 22 cm _____. Presidential decree nos. 228-317 and related documents,... Bk. three xxiv, 588 p. 22 cm